ANALISIS INTERNET FINANCIAL REPORTING (IFR) (Studi Pada Perusahaan Manufaktur Yang Go Public di Indonesia, Singapura, dan Malaysia) - Pratiwi Putri Widari Putri Widari; Muhammad Saifi; Ferina Nurlaily (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
Technological development become a part in every human life. Technology used because it is more effective in helping users including for companies in doing financial reporting. Internet Financial Reporting (IFR) is a voluntary disclosure of financial statements which measured using the Internet Financial Reporting (IFR) index. The purpose of this study are to know how the quality of Internet Financial Reporting (IFR) on manufacturing companies that go public in Indonesia, Singapore and Malaysia. The type of research is content analysis with quanlitative approach. Data analysis technique used descriptive analysis technique. The results of this study indicate that the quality of Internet Financial Reporting (IFR) at the go public manufacturing companies in Singapore is better than Indonesia, and Malaysia. The quality of the content components at the go public manufacturing companies in Singapore is better than Indonesia, and Malaysia. The quality of the timeliness component at the go public manufacturing companies in Singapore is better than Indonesia, and Malaysia. The quality of the technology component at the go public manufacturing companies Singapore is better than in Malaysia, and Indonesia. The quality of the user support components at the go public manufacturing companies Indonesia is better than in Singapore, and Malaysia. Kеywords: Internet Financial Reporting (IFR), content, timeliness, technology, user support. АBSTRАK Teknologi semakin berkembang dan menjadi bagian dalam kehidupan manusia Teknologi digunakan karena lebih efektif membantu keperluan penggunanya termasuk bagi perusahaan dalam melakukan pelaporan keuangan. Internet Financial Reporting (IFR) merupakan pengungkapan laporan keuangan secara sukarela melalui website perusahaan yang kualitasnya diukur menggunakan indeks Internet Financial Reporting (IFR). Tujuan dari penelitian ini adalah untuk mengetahui bagaimana kualitas Internet Financial Reporting (IFR) secara keseluruhan dan tiap komponennya pada perusahaan manufaktur yang go public di Indonesia, Singapura dan Malaysia. Jenis penelitian yang digunakan adalah penelitian analisis isi dengan pendekatan kuanlitatif. Teknik analisis data yang digunakan adalah teknik analisis deskriptif. Hasil dari penelitian ini menunjukkan bahwa kualitas Internet Financial Reporting (IFR) pada perusahaan manufaktur yang go public di Singapura lebih baik daripada di Indonesia, dan Malaysia. Kualitas pada komponen Content pada perusahaan manufaktur yang go public di Singapura lebih baik daripada di Indonesia, dan Malaysia. Kualitas pada komponen Timeliness pada perusahaan manufaktur yang go public di Singapura lebih baik daripada di Indonesia, dan Malaysia. Kualitas pada komponen Technology pada perusahaan manufaktur yang go public di Singapura lebih baik daripada di Malaysia, dan Indonesia. Kualitas pada komponen User Support pada perusahaan manufaktur yang go public di Indonesia lebih baik daripada di Singapura, dan Malaysia. Kаtа Kunci: Internet Financial Reporting (IFR), content, timeliness, technology, user support.